2022
DOI: 10.3389/fped.2022.980024
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula versus continuous positive airway pressure in primary respiratory support for preterm infants: A systematic review and meta-analysis

Abstract: Respiratory support is crucial for the survival of preterm infants, and High-flow Nasal Cannula Oxygen Therapy (HFNC) and Continuous Positive Airway Pressure (CPAP) are commonly used for neonatal respiratory support. This meta-analysis aimed to compare the effects of HFNC and CPAP in primary respiratory support for preterm infants, to provide evidence-based support for clinical practice. PubMed, Embase, Cochrane Library, ClinicalTrials.gov, CNKI, VIP, WANFANG and SinoMed were searched for eligible studies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…However, that study is not comparable with the present trial since the occurrence of NEC was 5- to 10-fold higher and the antenatal corticosteroids rate was 4- to 5-fold lower . A recent meta-analysis supports this hypothesis, reporting that earlier FEF was reached with HHHFNC compared with NCPAP as the primary respiratory support . However, the authors emphasized the high heterogeneity of the results, suggesting that results might be affected by the lack of protocols and other undetected bias.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, that study is not comparable with the present trial since the occurrence of NEC was 5- to 10-fold higher and the antenatal corticosteroids rate was 4- to 5-fold lower . A recent meta-analysis supports this hypothesis, reporting that earlier FEF was reached with HHHFNC compared with NCPAP as the primary respiratory support . However, the authors emphasized the high heterogeneity of the results, suggesting that results might be affected by the lack of protocols and other undetected bias.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies comparing NCPAP and HHHFNC have reported data on their possible effects on enteral nutrition. Although these data were conflicting, a recent meta-analysis suggested the benefits of HHHFNC vs NCPAP for feeding tolerance . Despite the effects of different types of NRS on nutrition and growth of very preterm infants, no randomized clinical trial has been specifically conducted to assess such outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…While in the literature, MV and HFNC are the therapies most commonly associated with ROP [ 7 , 8 , 14 , 44 , 45 ], in our study it was the less reputed ROP risk factor, namely nCPAP, that had the strongest correlation with ROP incidence, while MV and HFNC were not significant risk factors at any level of analysis. This is especially surprising following the results of a recent systematic review, in which the pooled results of a meta-analysis of 3 studies comparing nCPAP and HFNC in terms of risk of ROP were not statistically significant [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review and meta-analysis has been published with the aim to compare HFNC versus nCPAP as primary respiratory support in preterm infants to provide evidence-based support for clinical practice [ 46 ]. The primary outcome considered was the incidence of treatment failure and the need for MV after non-invasive respiratory support.…”
Section: Noninvasive Respiratory Support Of the Preterm Infants In Th...mentioning
confidence: 99%